If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) = x + -13 Reorder the terms: 2(-1 + 3x) = x + -13 (-1 * 2 + 3x * 2) = x + -13 (-2 + 6x) = x + -13 Reorder the terms: -2 + 6x = -13 + x Solving -2 + 6x = -13 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2 + 6x + -1x = -13 + x + -1x Combine like terms: 6x + -1x = 5x -2 + 5x = -13 + x + -1x Combine like terms: x + -1x = 0 -2 + 5x = -13 + 0 -2 + 5x = -13 Add '2' to each side of the equation. -2 + 2 + 5x = -13 + 2 Combine like terms: -2 + 2 = 0 0 + 5x = -13 + 2 5x = -13 + 2 Combine like terms: -13 + 2 = -11 5x = -11 Divide each side by '5'. x = -2.2 Simplifying x = -2.2
| 6x-3y=48 | | 2x+1-2(x+1)=5x+7 | | 81k^3+24m^3= | | -4(5+8u)+2=38-4u | | 9x-45+7=-16+8x | | -4(5+8u)+2=38-4 | | 3x+16=-10-(2x-6) | | 90+.30x=50+.70x | | 6Q-11=5 | | 6(1)-5+2(1-2)=x | | -8-x=1 | | n^2-11+10=0 | | 2x-5-6-2x=11 | | -26d=-36a | | 90+30x=50+70x | | .33(50+x)=80 | | 128x^3-2x^5= | | -3s+(-5s+1)= | | -3s+(-5s+1)= | | -12-x=-2(x+4) | | 90x+30x=50+70x | | 12t+5t=6(t+2) | | 6Q-30-19=5 | | 90p=100+70p | | 1.7b=39.1 | | 3x+1=-9-5x | | 3(m+5)-6=3m+3 | | 6b+10=3b+9 | | 9d+15-4d-8-5d= | | 7x-7x=-10x-20+35-5x | | 4x=3y-1 | | 9x+15-8x=-2-11 |